Study on the Effects of Aluminum and Chromium on the Corrosion Resistance of Hot-Rolled Incoloy 800H Alloy in Molten Carbonate Salts - CAO Junjia, YU Haicun, GAO Yunteng, LI Haixiao, LI Yafeng, XU Shipeng, LA Peiqing (Cailiao Baohu)
Metal alloys are subjected to molten salt corrosion in concentrating solar thermal power systems， leading to a reduction in their lifetime.In order to extend the service life of Incoloy 800H alloy in molten carbonate salt corrosion， Incoloy 800H alloys with varying aluminum(Al) and chromium (Cr) contents were prepared by vacuum induction melting.The corrosion mechanisms of Al and Cr elements on the resistance of 800H alloy to molten carbonate salt corrosion were investigated through analysis and testing methods such as X-ray diffraction (XRD)，scanning electron microscopy (SEM) and transmission electron microscopy (TEM).Results showed that the corrosion rate of Incoloy 800H alloy with 3%(mass fraction， the same below) Al content was 1 071.00 μm/a， while that with 2.75%Cr content was 359.56 μm/a after immersion in carbonate molten salt (32.1%Li2CO3＋33.4%Na2CO3＋34.5%K2CO3) at 650 ℃for 240 h.The corrosion products were mainly LiFeO2 and NiO.This was attributed to the fact that as the Al content increased， the oxide passivation film formed on the surface of the alloy became thicker and denser， providing better protection.The reduction of Cr content led to a decrease in the generation of soluble Cr oxides， an increase in the formation of other protective oxides， and a reduction in the precipitation of Fe elements in the substrate， thus improving the alloy’s corrosion resistance.